Revitalisasi Bahasa Banjar melalui Pelatihan Guru Master Tingkat Sekolah Menengah Pertama - Ida Komalasari; Noor Indah Wulandari; Muhammad Saufi; Vivi Aulia; Lili Agustina (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2026)
This community service activity aims at revitalizing the Banjar language through a workshop for 40 secondary school teachers. This activity engages the Universitas PGRI Kalimantan students as the social agents of local language learning at school. This activity employed five stages of workshop-based practice: preparation session, training session, implementation session, reflection session, and evaluation session. Based on the pre-test and post-test scores, there was an increase in the participants’ scores. The lowest pre-test score was 60, and the highest one was 90, with an average pre-test score of 70.3. Meanwhile, the lowest post-test score was 80 and the highest was 100, with an average post-test score of 96.5. The result of the questionnaire also indicates an increase in teachers’ performances. They performed very well. Overall, the results of the activity showed that teachers were able to understand the structure of the Banjar language. They were able to compose Banjar language speech texts systematically, improve their Banjar speech with more confidence, and produce speech documentation in the form of digital scripts and video recordings. In addition, the teachers were able to act as facilitators and mentors for other teachers in their respective schools.